Consumer social values - Gurel-Atay, Eda ;Kahle, Lynn R. (New York : Routledge, 2019)
Social values are central to people$1 (Bs lives, guiding behaviors, and judgments, and defining who we are. This book advances understanding of consumer social values and their roles in the global marketplace by refining and directing existing knowledge of consumer behaviors. The book introduces innovative concepts and provides comprehensive coverage of several specialized areas, to offer an important contribution to values research and discussion. Key topics include values and choice; means-end chains; relations among goals; motives; religion and personality; value measurement and values related to specific services and industries. s
SECTION I. Key Issues in Social and Cultural Values -- SECTION II. Specific Applications of Values Research and Theory -- SECTION III. Spiritual Aspects of Values -- SECTION IV. Methodological Approaches.
Includes index.
Keywords: CONSUMER BEHAVIOR